Inhibition on color changes of raja banana (Musa sapientum) peel using specific acid. Issue 1 (April 2021) - Al-Baarri, A N; Legowo, A M; Widayat,; Rizqiati, H; Hintono, A; Pramono, Y B; Somantri, M; Broto, W; Hadipernata, M; Santosa, V C; Permatasari, T P A; Salam, R H; et al.
Abstract: Banana is a tropical fruit that has high nutritional contents such as carbohydrates, vitamins and minerals, but it is prone to enzymatic browning reactions due to polyphenol oxidase (PPO) activity. This research was conducted to inhibit the reduction of the lightness of banana flesh using Hypoiodous Acid (HIO) as specific acid. The banana peel was stored for 3 days at room temperature storage (27°C). The analysis was done on colour change based on the L* value. HIO was obtained using a reaction mixture between H2 O2 and KI using peroxidase as a catalyst. The HIO was attached to the crown surface of the banana. The lightness was analysed using a digital colour meter within seven points of the area. The results showed that HIO could inhibit the lightness change of banana flesh resulting in a non-significant decrease in the lightness during 3 days of storage. This research might open the knowledge of the preservation of bananas by inhibition of its lightness change in the end-user banana consumer.